Keterlibatan Voluntourist dalam Pelaksanaan Konservasi Terumbu Karang di Pantai Tianyar, Kecamatan Kubu, Kabupaten Karangasem - Widyantari, Ni Putu Ayu; Sukana, Made (JURNAL DESTINASI PARIWISATA; Vol 9 No 1 (2021): VOL 9, NO 1 (2021): (JANUARY-JUNE) JURNAL DESTINASI PARIWISATADO - 10.24843/JDEPAR.2021.v09.i01.p23, 2021)
As the Island of God Bali is favorite tourism destinations in Indonesia. It has many tourist attractions can found in Bali like art tourist, beauty nature, and the others. One of them is Tianyar Beach located in Tianyar Village, Kubu District, and Karangasem Regency. It is very natural beach and has a beauty of coral reefs. There are several activities that could be done by tourists in Tianyar Beach, such as fishing, diving, and snorkeling. It also has black sand that is suitable for health therapies, reduce aches and back pain, and to relax the neck muscles, waist and blood circulation. For some tourist may come for sunbathing only and relaxing their body. However, the damage of coral reefs happened in Tianyar, Les, and Pemuteran Beach in the year of 1990s. It caused by 2 (two) main factors that is natural and human reasons. The natural factors are the climate chance, abrasion, and the occurrence of strong waves that cause the destruction of coral reefs. The human factor is an unsustainable fishing by using the unfriendly tools for the environmental (i.e. dynamite, electric, and pesticide. The damage of coral reefs also caused by ignorance of the local people to use the coral reefs as building materials. They used coral reefs to make a limestone to build houses. The damage of coral reef encourages I Ketut Sujana, the young local activist, to conserve the environment. He involves the volunteers to participate on several programs. He motivated to do conservation by seeing the bad condition of coral reefs, unsustainable fishing and reduced catches of fish. He was also motivated by seeing a correlation between conservation activity and people, when this activity is able to process their owned resources, then it will have social and economic impacts. Then He established a foundation called “Yayasan Bakti Segara “in 2012 which was assisted by group of fishermans an Voluteers. They build an artificial coral structure with the materials of sand, cement, and calcium carbonate. The making is done every day. From those materials, they make it in various form (i.e. turtle, flowers, tree, etc.). Then left it to harden. The artificial coral moved to the beach on Wednesday, to be dried in the sun to make it harder, then it will be submerged on every Thursday depend on the situation of the beach. It is planted about 5 until 10 meters in the ocean, where they are still exposed to sunlight. The content of water and sunlight enables the coral reefs to grows well. When it is ready, the artificial coral will be transported by boat to the designated conservation area. The people who participate will dive in and arrange the location and position of the coral according to the standard of Yayasan Bakti Segara. Local fishermen also support these activities. They become the members of organization and participate of all conservation programs. There are 20 members in it. They used to be peoples who often helped Mr. I Ketut Sujana, so they invited to be a member, because they knew the situation and condition of the beach. Keyword: conservation, coral reefs, participation, voluntourist, voluntourism.